Short‐chain fatty acids enhance muscle mass and function through the activation of mTOR signalling pathways in sarcopenic mice - Chaoran Liu; Pui Yan Wong; Qianjin Wang; Hei Yuet Wong; Tao Huang; Can Cui; Ning Zhang; Wing Hoi Cheung; Ronald Man Yeung Wong (Journal of Cachexia, Sarcopenia and Muscle)
Abstract Background Sarcopenia is a prevalent muscle disorder in old people leading to higher fracture rate, mortality, and other adverse clinical outcomes. Evidence indicates that short‐chain fatty acids (SCFAs), which are beneficial gut microbial metabolites, were reduced in old people with sarcopenia. This study aimed to determine whether the use of SCFAs as a supplement can be a therapeutic strategy of sarcopenia in a pre‐clinical model. Methods Seven‐month‐old pre‐sarcopenic senescent accelerated mouse prone 8 (SAMP8) mice received daily SCFAs cocktail (acetate, butyrate, and propionate) for 3 months. Age‐matched senescence accelerated mouse resistant 1 (SAMR1) and SAMP8 mice receiving sodium‐matched drinking water were control groups. The gut microbiota composition analysis of aged mice with or without sarcopenia was conducted by 16S rDNA sequencing. Gut barrier‐related proteins and lipopolysaccharide (LPS) concentration were biomarkers of gut permeability. Colon inflammation levels, circulatory SCFAs concentration, muscle quality, function, and underlying pathways were detected by cell number counting, RT‐qPCR, gas chromatography–mass spectrometry, measurements of muscle wet weight and grip strength, ex vivo functional test, treadmill endurance test, transcriptomic sequencing, morphological and immunofluorescent staining, as well as western blot. To investigate the role of mTOR signalling pathways in SCFAs treatment, C2C12 myotubes were treated with rapamycin. Results Aged SAMP8 mice had different microbiota composition, and lower serum butyric acid compared with SAMR1 mice (P < 0.05). SCFAs treatment reversed the increment of colon inflammation (2.8‐fold lower of il‐1β) and gut barrier permeability (1.7‐fold lower of LPS) in SAMP8 mice. Increased muscle mass, myofibre cross‐sectional area, grip strength, twitch and tetanic force were found in SCFAs‐treated mice compared with control SAMP8 mice (P < 0.05). Anti‐fatigue capacity (1.6‐fold) and muscle glycogen (2‐fold) also improved after SCFAs treatment (P < 0.05). Transcriptomic analysis showed that AMPK, insulin, and mTOR pathways were involved in SCFAs treatment (P < 0.05). Regulation of AKT/mTOR/S6K1 and AMPK/PGC1α pathways were found. SCFAs attenuated fat infiltration and improved mitochondria biogenesis of atrophic muscle. In vitro studies indicated that SCFAs inhibited FoxO3a/Atrogin1 and activated mTOR pathways to improve myotube growth (P < 0.05), and rapamycin attenuated the effect of SCFAs through the inhibition of mTOR pathways. Conclusions This study demonstrated that bacterial metabolites SCFAs could attenuate age‐related muscle loss and dysfunction, and protein synthesis‐related mTOR signalling pathways were involved both in vivo and in vitro.